Respuesta :

jsff42
first find g(-4) 
so :
g(-4) = (-4) + 5 
g(-4) = 1 

then find f(g(-4)) which means to substitute the value of g(-4) in for x in f(x) 
so:
f(1) = 1^2 - 13
f(1) = 1 -13 
f(1) = -12 

Answer:

The value of  [tex]f[g(-4)][/tex] is, -12

Step-by-step explanation:

Given the functions:

[tex]f(x) = x^2-13[/tex]

[tex]g(x) = x+5[/tex]

We have to find the value of [tex]f[g(-4)][/tex]

Substitute the value of x = -4 in g(x) we have;

[tex]g(-4) = -4+5 = 1[/tex]

Now;

[tex]f[g(-4)] = f[1][/tex]

then;

[tex]f[g(-4)] = (1)^2 -13 = 1-13 = -12[/tex]

Therefore, the value of  [tex]f[g(-4)][/tex] is, -12

ACCESS MORE